MicroRNA-543 in systemic diseases and possible applications in gynecologic tumors - Yan-Ran Sheng (Reproductive and Developmental Medicine, 2021)
In recent years, an increasing number of young women have been diagnosed with cancer, including some nulliparous women. Therefore, many young patients with early-stage cancer desire to preserve fertility after cytotoxic oncological treatments. It is important to develop a multidisciplinary approach to achieve the best outcomes for each patient. On the other hand, there has been a sharp increase in microRNAs (miRNAs) as potential biomarkers for the diagnosis, prognosis, and evaluation of treatment efficacy of several diseases. MiR-543 has been reported to affect the pathogenesis and progression of diseases via complex mechanisms. Understanding the regulatory role of miR-543 may aid comprehension of the pathogenesis and treatment of a broad range of diseases. Therefore, we provide an overview of the biogenesis, function, and role of miR-543 in various systems. These results shed light on the anticancer and endometrial protection role of miR-543 in young patients with gynecologic tumors and highlight the clinical potential of miR-543-based applications and related challenges.